One-year experience with 68Ga-PSMA PET/CT: applications and results in biochemical recurrence of prostate cancer - Prado Júnior,Luciano Monteiro (2018)
Abstract Objective: To show the initial (first-year) experience with 68Ga-PSMA PET/CT at a clinic in Brazil. Materials and Methods: Over a one-year period, 96 examinations with 68Ga-PSMA PET/CT (85 related to prostate cancer and 11 related to kidney cancer) were performed in 90 patients. Results: In the prostate and kidney cancer patients alike, the main clinical indication for 68Ga-PSMA PET/CT was suspicion of recurrence during follow-up (in 65.8% and 63.0% of the cases, respectively). Among the prostate cancer patients, 38.5% of those with a prostate specific antigen (PSA) < 0.5 ng/mL tested positive for recurrence on 68Ga-PSMA PET/CT, compared with 71.0% of those with a PSA of 0.5-0.99, 85.7% of those with a PSA of 1.0-1.99, and 92.6% of those with a PSA > 1.99. Conclusion: Although 68Ga-PSMA PET/CT is a technique that has only recently been applied in clinical settings, despite its high cost, 68Ga-PSMA PET/CT shows great promise as a tool in the clinical management of patients with kidney and prostate cancer, especially in those with prostate cancer whose PSA levels are elevated even after treatment.